Continental crossroads : remapping U.S.-Mexico borderlands history - Truett, Samuel, 1966-; Young, Elliott, 1967- (American encounters/global interactions., 2004)
Essays explore a transnational vision of the U.S./Mexico borderlands, and analyze this region's race, class, and gender inequalities in historical perspective.